O uso da água em Goiás, potencialidade, demanda para irrigação por pivôs centrais e perspectivas - Pereira Júnior, Lindolfo Caetano (2017)
In this paper, an analysis of expansion of central pivots irrigation in the estate of Goiás from 1984 to 2015 was performed, with the objective of identifying the conditioning factors of this occupation process and its relation with the water compromise in the study area. For this, images obtained by Landsat satellite sensors and Government data were used to map these facilities. In order to define the water compromise, we also mapped the existing equipment in the Distrito Federal. In addition, was used as reference the Medium Long Term Flow (QMLT), generating a scenario of maximum hydrological potential. As final phase, was performed the analysis of the commitment in catchment basins for public supply, having as a reference the max water right capacity. The state had 3,489 facilities covering an irrigated area of 242,128 hectares in 2015. There was a clear pattern of distribution of irrigation pivots within the state, 60% of existing equipment are located on flat relief terrain with latosols and as close as 10 kilometers of a paved highway. This technique is consolidated in Goiás and tends to expand in the coming years, being a gradual and continuous expansion that facilitates long-term water resource management action. The mapped equipment is located in mid-priced land areas, more distant from the major urban centers, however with the required infrastructure for the production distribution. The area of study (Goiás and Distrito Federal) presented an average water availability in the order of 17 l.s-1 (km²)-1 with a maximum around 32 l.s-1 (km²)-1 and a minimum around 9 l.s-1 (km²)-1 . This availability is distributed in a heterogeneous manner, with the largest flows being in the south of the state of Goiás. The annual surface hydrological potential in the study area is of the order of 178 km³.year-1 . For the state of Goiás, this potential is around 175 km³.year-1 and for the Distrito Federal is approximately 2.5 km³.year-1. The hydrographic region that presented the highest potential volume was the Corumbá, Verissimo and São Marcos rivers, with an offer of the order of 26 km³.-1, a volume that represents about 15% of the total. The average volume required for irrigation by central pivots was 4,800 m³.year-1 .ha-1 , ranging from about 3,800 m³.year-1 ha-1 in the south to around 8,000 m³.year-1.ha -1 in the northeast of Goiás; Resulting in a demand of 1.23 km³-year, with reference to the year 2015. About 68,857 (85%) of the segments analyzed do not present any interference generated by this irrigation sector. This technique also does not present itself as a factor of pressure on the pumping for human supply (using the methodology adopted for granting in Goiás) since only one hydrographic basin presented demand superior to QMLT.